2022
DOI: 10.1177/00405175221104264
|View full text |Cite
|
Sign up to set email alerts
|

Study of superhydrophobicity according to surface structure of knitted fabrics

Abstract: This study seeks to analyze the effect of geometric structures of weft-knitted fabrics on superhydrophobicity and the dynamic behavior of water droplets. A flat knitting machine with different stitch patterns was used to prepare 100% polyester knitted fabrics. For the superhydrophobic surface, nano-roughness through alkaline treatment and a hydrophobic coating were introduced on prepared knitted fabrics. To analyze micro-roughness, pore size, cover factor, surface roughness, and air permeability were measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The superhydrophobic surface keeps fog condensed on the surface in a very good spherical shape. Low RA of the surface makes a spherical droplet fall easily …”
Section: Superwettable Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The superhydrophobic surface keeps fog condensed on the surface in a very good spherical shape. Low RA of the surface makes a spherical droplet fall easily …”
Section: Superwettable Surfacementioning
confidence: 99%
“…Low RA of the surface makes a spherical droplet fall easily. 69 Based on the rapid droplet rolling property of a superhydrophobic surface, a fog harp consisting of vertical metal wires is designed for fog collection, 70 as shown in Figure 5a−c. Experimental results demonstrate that the FCR consistently increases with a decreasing wire diameter, attributed to the effective droplet shedding on the superhydrophobic surface, which prevents clogging.…”
Section: Theoretical Basismentioning
confidence: 99%
“…The authors showed that a difference in the surface roughness of the material of more than 0.43 mm can lead to differences in the color appearance of the product, which in turn can lead to a negative perception by the consumer or wearer of the product. The study conducted by Lee [ 6 ], which focused on the influence of different patterns on the roughness of 100% polyester knitted fabrics, indicated higher values for tuck, purl, and plain jersey stitch patterns. As far as the influence of aging on the changes in polymer materials is concerned, the measurements on the FTT tester have shown that the properties of standard and artificially aged polyester fabric (aging duration 85 h) differ significantly.…”
Section: Introductionmentioning
confidence: 99%